Metabolite perturbations in type 1 diabetes associated with metabolic dysfunction-associated steatotic liver disease - Taiwo, Adeyinka; Merrill, Ronald A.; Wendt, Linder; Pape, Daniel; Thakkar, Himani; Maschek, J. Alan; Cox, James; Summers, Scott A.; Chaurasia, Bhagirath; Pothireddy, Nikitha; Carlson, Bianca B.; Sanchez, Antonio; et al. (Frontiers in Endocrinology, 2025)
BackgroundMetabolic dysfunction-associated steatotic liver disease (MASLD), formerly called non-alcoholic fatty liver disease (NAFLD) is the hepatic manifestation of the metabolic syndrome. Although MASLD has been widely studied in persons with Type 2 diabetes (T2D), far less in known about the pathogenesis and severity of MASLD in Type 1 diabetes (T1D).ObjectivesDetermine metabolic perturbations associated with MASLD in persons with T1D.Study DesignWe conducted a cross-sectional study of 30 participants with T1D. Based on the results of a FibroScan, participants were stratified as cases (MASLD) or controls. Metabolomic analyses were performed on plasma obtained from all participants after an overnight (after midnight) fast.Results17 of 30 participants were classified as cases (MASLD) and 13 as controls. Cases had higher BMI (p=<0.001) and were taking higher daily insulin doses than controls (p=0.003). Metabolomic analyses revealed that those with MASLD had elevated levels of gluconeogenic substrates pyruvate (p=0.001) and lactate (p=0.043), gluconeogenic amino acids alanine (p<0.001) and glutamate (p=0.004), phenylalanine (p=0.003), and anthranilic acid (p=0.015). Lipidomics revealed, elevated ceramides (P=0.02), diacylglycerols (p=0.0009) and triacylglycerols (P=0.0004) in MASLD group. In those with MASLD, the acylcarnitines, isovalerylcarnitine (CAR.5.0) (P=0.002) and L-Palmitoylcarnitine (CAR.16.0) (P=0.048), were elevated. Pathway analyses using MetaboAnalyst 5.0 Software revealed that, pathways including phenylalanine and tyrosine metabolism, tryptophan metabolism, glucose-alanine cycle, glutamate metabolism, and glutathione metabolism were significantly enriched in those with MASLD.ConclusionParticipants with T1D and MASLD manifest features of insulin resistance and metabolite perturbations suggesting enhanced gluconeogenesis, dysfunctional fat synthesis, and perturbed TCA cycle activity.